Análise da regularização do cultivo em tanque-rede e o transporte da tilápia - COELHO, Thamiris T. L. A. (2018)
The State of Minas Gerais has several reservoirs and, among them, the Reservoir of Furnas is one of the largest artificial lakes in the world. There, it were detected 130 units tilapia fish farming net, favorite production specie in Brazil. Surveys, carried out by EPAMIG (state department) and the Ministry of Fisheries, have demonstrated that the hard way to be a legal producer as the activity barrier. Being legal brings legal recognition, makes it possible creating a brand and retain clients, hiring employees as a company, issuing invoices, obtaining financing, incentives and exemptions, contributing a sustainable environment, participating in bids and, first of all, working with no enforcements and penalties scares. The main goal of this issue is to present the procedure needs for legal tilapia fish farming net in reservoirs and the live tilapia transportation within the State of Minas Gerais. Legislation differs according to the dominance of water. The document demand of different public bodies makes the fish farming net regulation processes time-consuming and costly. Therefore, many owners have no option, avoiding the legal business. In order to produce in Federal jurisdiction, the Environmental License is required, issued by the Regional Environment Authority, the General Register of Fishing Activity and the Use authorization of the Physical Spaces in water Bodies of Union Dominion issued by the Aquaculture Secretariat and Fisheries, and the granting of Water issued by the National Water Agency. If the dominion belongs to the State, it is necessary the aquaculture register, issued by the State Institute of Forests, the Granting of Water Use, issued by the Mining Institute of Water Management and the Environmental License, issued by the Regional Superintendence of Environment. In order to transport live tilapia, the Rural Producer Register and the Aquaculture Establishment Register emited by the Minas Gerais Agriculture Institute are required, as well the Animal Transit Guide. It is concluded that to set the tilapia fish farming net process, although necessary for environmental protection purposes is complex, bureaucratic, time-consuming and expensive.